Structurally-controlled fluvioglacial erosion features near Schefferville, Québec - Barr, William (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1969)
The coincidence as to location of a late-Wisconsin ice disintegration centre, with an earlier ice dispersal centre, some 30 miles north-west of Schefferville, Québec, resulted in large scale englacial meltwater flow from north-north-west to south-south-east across the Schefferville area. The direction of flow was controlled by the englacial hydraulic gradient, controlled in turn by the ice surface gradient. The Schefferville area is underlain by Proterozoic metasediments, exhibiting a series of parallel folds and thrust-faults aligned NW-SE ; this structure is reflected in the marked parallelism of the ridges and valleys. When the englacial meltwater streams were let down on to this substrate, structurally controlled alignment of the meltwater channels resulted. Generally, this has resulted in remarkably straight channels aligned along the strike or along faults. In the Houston Mountain area, however, steeply pitching anticlinos in slates oroduced a striking series of subglacial arcuate channels. At several points in the Schefferville area, subglacial meltwater flow down a hillside at right angles to the strike, and in the opposite direction to the dip, in zones of steeply dipping, well-bedded sediments, has produced the features referred to in literature as vallons, and earlier explained as being largely periglacial in origin. These are a special type of structurally controlled subglacial chute, in which there has been only slight periglacial modification of the original fluvioglacial form.